Análise numérica do acoplador duplo não-linear baseado em fibras de cristais fotônicos (NLDC-PCF) operando com PAM e PWM para obtenção de portas lógicas - Costa, Marcos Benedito Caldas (2013)
We present a numerical analysis for obtaining all-optical logic gates based on a nonlinear directional coupler symmetric (NLDC) based on photonic crystal fibers (PCF). The most commonly used to project the NLDC-PCF is a holey fiber, used here in cross section which is a periodic array of air holes extending through the length of the fiber, using two ultrashort light pulses in form of solitons, the minimum duration of 100fs (femtoseconds). We investigated two forms of modulation pulse, pulse amplitude modulation (PAM) in the form of amplitude shift keying (ASK) modulation and pulse width modulation (PWM) for logic gate NLDC-PCF symmetrical double. We evaluated the effect resulting from an increase in the offset parameter encoding PAM (ε) and PWM (w), considering the second order dispersion (β2), the third order dispersion (β3) and non-linear modulation effects SPM (Self Phase Modulation), SS (Self-Steepening) and IRS (lntrapulse Raman Scattering) in a configuration without loss. Our results indicate that logical operations can be obtained using a phase control between the input pulses.